2013
DOI: 10.1080/19371918.2011.593462
|View full text |Cite
|
Sign up to set email alerts
|

African American Women Living with Mental Disorders: Factors Associated with Help Seeking from Professional Services and Informal Supports

Abstract: This study utilized data from the National Survey of American Life to investigate the use of professional services and informal support among Black women with a lifetime mood, anxiety, or substance use disorder. Forty-seven percent combined professional services and informal support, 14% relied on professional services only, 2% used informal support only, and 16% did not seek help. Co-occurring disorders, recent episodes, social networks, marital status, age, and level of education were significantly related t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
11
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 37 publications
(37 reference statements)
1
11
0
Order By: Relevance
“…These socially vulnerable subgroups are also more likely to have a diagnosis of at least one mental disorder, which may, in turn, explain higher service use (66,67). As in previous studies (17,68), gender was a significant predictor of service use across samples. The suggestion is that young women may be more distressed than young men (3) and better at self-monitoring-and thus more likely to share problems with professionals (69).…”
Section: Discussionsupporting
confidence: 60%
See 3 more Smart Citations
“…These socially vulnerable subgroups are also more likely to have a diagnosis of at least one mental disorder, which may, in turn, explain higher service use (66,67). As in previous studies (17,68), gender was a significant predictor of service use across samples. The suggestion is that young women may be more distressed than young men (3) and better at self-monitoring-and thus more likely to share problems with professionals (69).…”
Section: Discussionsupporting
confidence: 60%
“…However, data related to evaluated need suggested that in clinical samples, diagnosis of a mental disorder was not independently associated with use. The strength of such an association may vary with psychiatric comorbidity and illness severity (17,20,72,73). These results may also reflect the use of diverse self-report inventories, with different cutoff scores determining symptom severity and clinical cases.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the first part of the analyses, three separate dependent variables were used. As seen in other studies, examining help-seeking behaviors for depression (Khazanov, Cui, Merikangas, & Angst, 2015;Sosulski & Woodward, 2013;Woodward, Taylor, & Chatters, 2011), the question "Did you ever in your life talk to a professional about your sadness/discouragement/lack of interest?" was used to assess past helpseeking behaviors, specifically for depression.…”
Section: Methodsmentioning
confidence: 86%